Bike, swim, mum: Exploring post partum experiences of triathlete mothers - Jones, E.; Stokes, K.; Du Preez, T. (Bangor University, 2024)
Athletes such as Serena Williams and Faith Kipyegon have justly dispelled the myth that motherhood is incompatible with elite sport. In parallel, we have seen an increase in post-partum return to sport research, which has guided specific post-partum guidelines such as Fallon et al. (2024). Whilst there has been an advancement in understanding the physical aspects (Donnelly et al., 2022), the psychological experiences are less well known and warrant further investigation to develop evidence-informed support that considers a holistic approach to return to sport post-partum. This is especially pertinent in sports such as Triathlon where athletes peak in their thirties, which coincides with the average age of motherhood (31 years, UK). Therefore, this research aimed to explore the psychological experiences of triathlete mothers, including investigating the key barriers and facilitators to postpartum participation. The qualitative study used a phenomenological approach grounded in social constructionism and ontological relativism to explore the lived postpartum experiences of 10 triathlete mothers (37.1 ± 4.9) using semi-structured interviews. The interviews were analysed using thematic analysis and the experiences of the participants were split into the nine sub-themes. Findings suggest that expectations of motherhood often differ to reality in part due societal construction of the superwoman façade. Women who were able to continue with physical activity adopted proactive behavioural changes such as increased organisation and time efficiency, had partner support and used goal setting strategies. Results also suggest most were influenced by `ethic of care` and feelings of guilt, but those who remained most active navigated this by justifying physical activity was beneficial for their family unit as well as themselves. Structural and organisational barriers varied depending on athletic standard with childcare and access to facilities particularly problematic for recreational and developmental level athletes. The study demonstrates the complex and individual nature of the postpartum journey.